Diagnostic predicament of bilateral ovarian masses with rare and distinct histopathology - Mohan, Ruchika; Bhayana, Aanchal; Bagri, Neha; Misra, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Xanthogranulomatous oophoritis is a rare, peculiar, non-neoplastic, chronic inflammatory pathology that can mimic ovarian mass. Affected organ shows replacement of normal tissue with foamy histiocytes, multinucleate giant cells, neutrophils, fibroblasts, plasma cells and areas of necrosis within. Its aetiology is still unknown, and the final diagnosis is usually made through histopathological examination. The present case report describes an unusual presentation of simultaneous occurrence of Xanthogranulomatous oophoritis and fibrothecoma masquerading as bilateral tubo-ovarian masses in a post-menopausal female. Despite initial assumptions and suspicions of tubo-ovarian abscesses, surgical exploration revealed an unexpected pathology. Histopathological evaluation confirmed the diagnosis, emphasising the importance of vigilant and comprehensive assessment in atypical presentations.